Rotavirus and adenovirus in children evaluated for viral gastroenteritis at a single healthcare center in the Eastern Province of Saudi Arabia: A perspective of two decades - Ahmed K Alqurayn; Obeid E. Obeid; Khaled R. Alkharsah (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The aim of this study was to determine the distribution of rotavirus and adenovirus in pediatric patients evaluated for viral gastroenteritis in a hospital in the Eastern Province of Saudi Arabia for 22 years. MATERIALS AND METHODS: This was a retrospective study based in a secondary healthcare center in Saudi Arabia. Laboratory and demographic data were collected from hospital records for all pediatric patients (up to 14 years old) evaluated for viral gastroenteritis by rotavirus/adenovirus antigen detection kit from January 2000 to December 2022. Data were analyzed utilizing SPSS version 28.0. Categorical data were presented as frequency and percentages, whereas mean and standard deviations were computed for continuous variables. Chi-square test and t-test were used to determine statistical significance. RESULTS: The overall yields of antigen detection were 13.6% for rotavirus and 2.6% for adenovirus. Coinfection with both viruses was documented in 0.5% of the study population. Rotavirus was persistently detected in the past two decades with varying frequency, but the detection of adenovirus showed intervals of at least three consecutive years of zero confirmed cases. Before 2013, when the rotavirus vaccine was introduced in Saudi Arabia, rotavirus was much more prevalent than adenovirus (30% compared to 3.8% in 2010), but they became equally prevalent a decade after the introduction of the vaccine. Rotavirus gastroenteritis showed three different peaks in the year, in March, July, and December. Each peak was followed by a gradual decrease in prevalence before the next peak. Adenovirus, in contrast, was detected consistently around the year at rates between 2% and 5%. CONCLUSION: Rotavirus and adenovirus gastroenteritis have changed in prevalence in the past two decades. We found distinct seasonal patterns associated with rotavirus and adenovirus gastroenteritis. The utilization of virological testing for pediatric gastroenteritis with syndromic testing panels is to be encouraged to improve the knowledge of the true prevalence of enteric viruses.